Family socioeconomic status and the parent-child relationship in Chinese adolescents: the multiple serial mediating roles of visual art activities - Chunhai Gao; Endale Tadesse; Sabika Khalid (BMC, 2022)
Abstract Background In light of the recent policy reform in China, the present study aims to investigate the potential impact of family SES on the quality of the parent-child relationship (PCR) through the serial mediating role of participation in organized visual art activities in privately owned centers (VAA1) and parent-supervised visual art activities (VAA2) across genders. Method A cross-sectional study was conducted in anonymous province located in the southwestern part of China. A total of 1624 primary school students aged 7 to 14 years were recruited through a random sampling technique. Subsequently, anonymous survey responses were taken from all students. Multiple serial mediation analysis was performed by using AMOS 21.0 software to attain the primary aim of the study. Result According to the total sample model result, SES has a significant direct effect on the parent-child relationship (β = 0.47, p < 0.001), children's participation in VAA1 (β = 0.197, p < 0.001) and VAA2 (β = 0.269, p < 0.001). Moreover, the mediation model result indicates that SES has a stronger indirect effect on the parent-child relationship through a mediating role of VAA1 (βgirl = 0.08, p < 0.01; βboys = 0.04, p < 0.01) for female than male samples. However, the mediating effect of VVA2 between SES and the parent-child relationship in the female (β = 0.08, p < 0.001) and male (β = 0.08, p < 0.01) models is equal, although female gender is highly significant. Ultimately, the serial mediation analysis result affirms that the serially mediating role of VAA1 and VAA2 between SES and the parent-child relationship was equal across genders (βboys = 0.001, p < 0.001; βgirls = 0.001, p < 0.001). Conclusion Unlike previous studies, this study's multigroup model shows that both male and female children can equally restore their relationship with their parents by having substantial participation in both VAA1 and VAA2. Thus, parents ought to play the main role in facilitating and supporting children's visual art activities without parenting that shows a gender bias.